Faktor-Faktor yang Mempengaruhi Harga Saham dengan Dividen sebagai Variabel Moderasi: Studi Empiris Perusahaan LQ-45 di Bursa Efek Indonesia pada Masa Pandemi Covid-19 - Fhad Ibnu Sina Basharahil; Kamaliah; Andewi Rokhmawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to examine the factors that influence stock prices with dividends as a moderating variable: an empirical study of Lq-45 companies on the Indonesia stock exchange during the Covid-19 pandemic. This study aims to see and determine the factors that influence stock prices with dividends as a moderating variable: an empirical study of Lq-45 companies on the Indonesia stock exchange during the Covid-19 pandemic. The population in this study are LQ-45 indexed companies on the Indonesian stock exchange in 2020. In sampling using the following criteria: LQ-45 public companies listed on the IDX for the 2020 period, the sampled companies must issue financial statements in 2020, LQ-45 Companies listed on the IDX that have complete quarterly data needed in this study, LQ-45 Companies that survive the research year. There are 42 companies indexed LQ-45 on the Indonesian stock exchange that meet the sample criteria. This study was analyzed using Multiple Linear Regression Analysis. The results of this study state that partially has no effect on stock prices, inflation has no effect on stock prices, bi rate has no effect on stock prices, stock trading volume has no effect on stock prices, profitability has no effect on stock prices, dividends affect stock prices, dividends moderating but weakening the effect of the exchange rate on stock prices, dividends moderating but weakening the effect of inflation on stock prices, dividends moderating but weakening the effect of the bi rate on stock prices, dividends moderate and strengthen the effect of stock trading volume on stock prices, dividends moderate and strengthen the effect of profitability on prices stocks, simultaneously exchange rate, inflation, bi rate, stock trading volume, profitability affect stock prices and dividends are able to moderate simultaneously.